DESIGN AND FABRICATION OF AN OPTIMISED COAL-FIRED CRUCIBLE PIT FURNACE - TERNGU AKOR; Jafaru A. M; Garuba D. K. (Academy Journal of Science and Engineering)
The main aim of this work  was to upgrade the hole on the ground type of crucible furnace at the department of mechanical engineering workshop of the Nigerian Defence Academy into a more efficient and portable furnace that can be deployed even in a lecture room for heat treatment and other experimental work. This paper present the design, construction procedures and result of the test for evaluating the performance of the optimized coal-fired crucible pit furnace. The shell is made of a mild-steel sheet of 2mm thickness, lined internally with refractory bricks. A motorized blower is incorporated to provide sufficient air circulation and pressure for effective combustion of the coal. Thermocouples and a pressure gauge are also attached to the shell to monitor the internal conditions of the furnace. The top of the furnace is closed with a brick walled cover fitted with a pipe to avoid convectional and radiation losses but allow for easy escape of combustion gasses.The crucible furnace was tested.  It melted 2kg of aluminum- scrap in 18 minutes at a temperature of about 6620C. The furnace temperature was allowed to reach 7820C for the charge to completely melt and be fluid enough for casting. The thermal efficiency of the furnace is 14.7%.; indicating very good performance. Normally the thermal efficiency for pit furnace is between 4-19%.